Therapy of Dequalinium Chloride Vaginal Tablets in Pregnant Women with Vulvovaginal Candidiasis - Setyowatie, Lita; Larasaty, Nanda Shaskia (Indonesian Journal of Obstetrics and Gynecology, 2025)
Background: Vulvovaginal candidiasis (VVC) is a Candida infection on vulva and vagina region. The most common etiology is C. albicans. Besides being the risk factor for developing VVC, pregnancy also limits the possible medication. This report presents the efficacy of Dequalinium Chloride (DQC) on VVC during pregnancy due to C. albicans. Case: A third-trimester primigravidae, 27-year-old, complained first odorless thick curd-like consistency vaginal discharge accompanied with pruritus (VAS 9/10) and pain since 3 months prior to admission. Venerology examination showed erythema on the labia majora and a great amount of thick vaginal discharge on the labia minora, vaginal, and cervix area. Vaginal discharge examination using KOH 10% showed pseudohyphae. Gram examination found pseudohyphae and polymorphonuclear (PMN) cells >30 in the vagina, and pseudohyphae on the cervix’s discharge. VITEK-2 culture showed fluconazole-sensitive C. albicans. The patient was given DQC intravaginal tablets for 10 days and showed remarkable clinical and microscopic examination improvement. Conclusion: Intravaginal DQC is effective in treating pregnant patients with VVC. VVC in pregnancy should be treated appropriately to prevent perinatal adverse effects. Keywords: Vulvovaginal Candidiasis, dequalinium chloride, pregnancy, C. albicans